A Phenomenological Exploration Of Spiritual Encounters In Medan's Christian Communities - Pardede, Dewi Lestari; Pardede, Lukman; Marpaung, Rince; Siahaan, Monalisa Marta; Silalahi, Dewi Paulina; Alexander, Irving Josafat; Pardede, Gloria (STABN RADEN WIJAYA WONOGIRI, 2024)
This study examines the impact of phenomenological research on the capacity of Christian congregations in Medan City to embody and live out spiritual values in their daily lives, by exploring both the transformative potential offered and the challenges faced in integrating phenomenological insights into faith practices. The study employs a descriptive qualitative methodology rooted in a systematic literature review, gathering insights through literature that focuses on the experiences of church congregations in Medan City. The findings highlight potential pathways for integrating phenomenological studies to cultivate life values among Christian congregations, including addressing obstacles such as methodological unfamiliarity, limited resources, and access barriers in deepening the understanding and application of Biblical teachings. The study also reveals significant challenges, such as ethical considerations in raising congregational awareness of the enlightenment process, as well as limitations in data analysis that affect the effectiveness of delivering Biblical messages. This research underscores the importance of phenomenological learning as a means to enrich religious understanding among Christians, enabling them to confront and overcome challenges in practicing spiritual values and fostering love within the diverse socio-religious landscape of Medan City